2019
DOI: 10.1002/aenm.201901351
|View full text |Cite
|
Sign up to set email alerts
|

Extended “Adsorption–Insertion” Model: A New Insight into the Sodium Storage Mechanism of Hard Carbons

Abstract: Hard carbons (HCs) are promising anodes of sodium‐ion batteries (SIBs) due to their high capacity, abundance, and low cost. However, the sodium storage mechanism of HCs remains unclear with no consensus in the literature. Here, based on the correlation between the microstructure and Na storage behavior of HCs synthesized over a wide pyrolysis temperature range of 600–2500 °C, an extended “adsorption–insertion” sodium storage mechanism is proposed. The microstructure of HCs can be divided into three types with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
354
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 340 publications
(371 citation statements)
references
References 69 publications
(146 reference statements)
16
354
1
Order By: Relevance
“…Apart from the influence of MXene, both HC‐PVDF electrode and HC‐MX films exhibit typical Na‐storage behavior of HC, agreeing well with the adsorption‐insertion sodium storage mechanism . In the CV curves, a pair of sharp peaks appear at around 0.1 V, indicating the sodium insertion/extraction in the interlayer of the carbon materials.…”
Section: Resultssupporting
confidence: 71%
“…Apart from the influence of MXene, both HC‐PVDF electrode and HC‐MX films exhibit typical Na‐storage behavior of HC, agreeing well with the adsorption‐insertion sodium storage mechanism . In the CV curves, a pair of sharp peaks appear at around 0.1 V, indicating the sodium insertion/extraction in the interlayer of the carbon materials.…”
Section: Resultssupporting
confidence: 71%
“…The large and unchanged graphitic interlayer spacings (0.400 nm) indicate that this sample can satisfy the layer spacing variation caused by the intercalation of sodium ions. [ 31,46,53,54 ] Similar results are presented in Figure S10, Supporting Information. Sufficiently large graphitic layer spacings can alleviate the volume expansion during charge and discharge, facilitate rapid diffusion of sodium ions, and expose more active sites, endowing the hard carbon nanosheets with an excellent rate performance, large reversible capacity, and long lifespan.…”
Section: Figuresupporting
confidence: 80%
“…To unify these storagem echanisms, Sun et al established an extended adsorption-insertion model and revealed the relationship between charge-storage mechanism ands tructure of HC. [55] They obtained HCs with different microstructures by carbonizing fallen ginkgo leaves at different temperatures, ranging from 600 to 2500 8C. The development of the microstructure, as well as the charge-storage mechanism and performance, are shown in Figure 3f.A tl ow temperatures, the HC possesses ah ighly disordered structure with al arge interlayer distance (> 0.4 nm).…”
Section: Principle and Mechanismmentioning
confidence: 99%